Nutritional Aspects in Pediatric Tuberculosis Cases Among Children Aged 0-5 Years - Amanda Dwiayu Saraswati; Lu'lu Nafisah; Colti Sistiarani (Rumah Sakit Penyakit Infeksi Prof Dr. Sulianti Saroso, 2025)
Background: Children aged 0-5 years are the age group at the highest risk of contracting tuberculosis. This infectious disease is closely related to nutritional aspects in children. These aspects include nutritional intake, exclusive breastfeeding, nutritional status, and history of infectious diseases. This study aims to explore the nutritional aspects of pediatric tuberculosis cases among children aged 0-5 Years. Methods: This study employed a qualitative case-study approach, involving in-depth interviews with informants and document analysis. The study included five primary informants, namely mothers of children aged 0-5 years diagnosed with tuberculosis, and three supporting informants, comprising two village midwives and one tuberculosis program officer at Sumbang I Public Health Center, Sumbang Dist. Data analysis was conducted using thematic analysis. Results: Loss of appetite and weight loss were observed in toddlers after tuberculosis infection, which gradually improved with treatment. There was a balanced distribution between good and poor nutritional status among the toddlers. Tuberculosis bacteria can infect children regardless of nutritional status if the immune system is suboptimal. Children who received exclusive breastfeeding were still susceptible to tuberculosis infection. Conclusion: Mothers fulfilled the nutritional needs of toddlers. Nutritional status and exclusive breastfeeding did not directly influence the infection.